(untitled) (Fourth World Journal, 1990)
Written in 1990, this article examines the key issues and debates between Indigenous nations, states, and international organizations surrounding the content and adoption of the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP), proposed for the 1992 General Assembly. It explains how, after decades of the UN reinforcing the state system through resolutions, the rights of internally colonized peoples began to take center stage, leading to the proposal of UNDRIP. After presenting the full text of the draft declaration, the article analyzes comments from various entities on the definitions of terminology, the extent of rights and self-determination protected, correlations to other UN declarations, the tension between individual and collective rights, and methods of implementation and mediation. The article concludes by discussing these disagreements and the potential paths forward through the UN bureaucracy, where both sides viewed the draft as too much of a compromise. The author argues that as long as states equate Indigenous self-determination with secession, reaching agreement may not be possible. However, by ignoring these calls for self-determination states risks provoking conflict and further threatening their sovereignty.